CORRELATION BETWEEN THE PERCENTAGE OF HYPOCHROMIC ERYTHROCYTES AND FERRITINE LEVELS IN CHRONIC KIDNEY DISEASE PATIENTS UNDERGOING HEMODIALYSIS IN PKU BANTUL HOSPITAL - Seno Dwi Prasetyo; Linda Rosita; Utami Mulyaningrum (Berkala Kedokteran, 2022)
Abstrak: The incidence of CKD in the world is more than 500 million patients and up to 1.5 million patients need to undergo renal replacement therapy in the form of hemodialysis. Chronic kidney disease is inseparable from several complications, one of which is anemia. Confirmation of the diagnosis of anemia in CKD patients can be confirmed through various examinations such as the classic examination of serum ferritine levels, but ferritine is known to be involved in the inflammatory process that occurs in CKD. The aims of this study were to determine the relationship between the percentage of hypochromic erythrocytes and ferritine levels, to determine the average percentage of hypochromic erythrocytes and to determine the average ferritin level in CKD patients undergoing hemodiliasis at PKU Bantul Hospital. This study was conducted using a cross-sectional method involving 50 CKD patients at PKU Bantul Hospital. Blood samples were taken to check ferritine levels and hypochromic erythrocyte percentage. Data analysis was carried out with two types, univariate analysis and bivariate analysis which were carried out with the Spearman correlation test. Based on the results of univariate analysis, the median percentage of hypochromic erythrocytes of the research subjects was 0.95%. The median ferritine in research subjects was 105.5 ng/mL. based on the results of bivariate analysis, there was no significant relationship between the percentage of hypochromic erythrocytes and ferritine levels (p=0.130, r=-0.217). There was no significant relationship between the percentage of hypochromic erythrocytes and ferritine levels. Keywords: anemia; ferritine serum, chronic kidney disease, reticulocytes hemoglobin